2006
DOI: 10.1210/en.2005-0748
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Programmed Hyperleptinemia and Hypertension by Postnatal Dietary ω-3 Fatty Acids

Abstract: Fetal programming is now recognized as a key determinant of the adult phenotype, with major implications for adult-onset diseases including hypertension. Two mediators of fetal programming are maternal nutrition and fetal glucocorticoid exposure. Recent studies show that postnatal dietary manipulations can exacerbate programming effects, but whether programming effects can be attenuated by postnatal dietary manipulations, and thus provide a possible therapeutic strategy, is unknown. In this study, we tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 47 publications
12
93
0
Order By: Relevance
“…Evidence from clinical studies showed that 5% reduction in body fat percentage improved cardiometabolic risk profile in obese children (21) and adults (22). Very few experimental studies have focused on prevention of obesity and metabolic Few studies have shown that exposure to n3 long-chain polyunsaturated fatty acids throughout life protects against the detrimental effects of an adverse fetal environment on blood pressure, inflammation, leptin sensitivity, and glucose homeostasis in adult rats (26,27). In addition, n3 long-chain polyunsaturated fatty acid supplementation during pregnancy and lactation reduced BW of adult rat offspring on a standard chow by 5% (28).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from clinical studies showed that 5% reduction in body fat percentage improved cardiometabolic risk profile in obese children (21) and adults (22). Very few experimental studies have focused on prevention of obesity and metabolic Few studies have shown that exposure to n3 long-chain polyunsaturated fatty acids throughout life protects against the detrimental effects of an adverse fetal environment on blood pressure, inflammation, leptin sensitivity, and glucose homeostasis in adult rats (26,27). In addition, n3 long-chain polyunsaturated fatty acid supplementation during pregnancy and lactation reduced BW of adult rat offspring on a standard chow by 5% (28).…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies for reversal may also be possible. 63,64 It is the mismatch between the developmental trajectory chosen in response to the early-life signals and the later adipogenic environment that creates the added risk of obesity. It is interesting to note the broad nature of the induced phenotype, including altered food preference and appetite, alterations in intermediary metabolism including insulin resistance, and sarcopenia.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 99%
“…The role of possible direct nutritional interventions was highlighted in the work by Wyrwoll et al [161] . Pregnant rats were treated with DEX from d13 to term, and offspring were cross-fostered to mothers on either a standard diet or a diet high in omega-3 fatty acids and remained on these diets post-weaning.…”
Section: Critical Windows Of Development and Avenues For Interventionmentioning
confidence: 99%